Penerapan Layanan Khusus yang Mendukung Manajemen Peserta Didik di Sekolah Dasar Islam Terpadu SD IT Al-Munadi - Okta Elviana Manurung; Imay Ayu Salamah; Khansa Arista Widya Maulida; Mulia Ardiasyah Harahap; Muhammad Ilham (Journal on Education, 2023)
Management is one of the benchmarks that can support an achievement of results from activities that have been arranged or planned in an arranged manner so that they can produce a decision desired by any party referred to in the school. Students are one of the important factors in supporting educational activities. In the current era, the amount of competition that arises between schools can cause difficulties for schools to get new prospective students (students). As for the efforts that can be made by schools in supporting the growth and development activities of students, namely by having special services at school. These special services include guidance and counseling services, library services, canteen services, health services, school transportation services, hostel services. Extracurricular services, laboratory and security services. Special services provided by schools to students can support the implementation of educational teaching in schools so as to produce the desired goals. Management of special services is one of the activity processes to provide convenience to students by creating special services in schools so that they can support effective and efficient learning activities.